Paper microfluidics for clinical diagnostics using colourimetric detection methods - Dawson, Amy L. (2014)
Microfluidics is a technology currently aiming to advance the medical devices currently available in the developing and developed world through simultaneously creating point-of-care devices which are “as good” or better than current methods at a cheaper production cost. To be able to diagnose diseases and infections quickly and affordably remains the aim of many researchers and the use microfluidics has advantages which plug this difficulty. However, one main gap in the research is to train users for these devices which give accurate results when compared to current methods. Described herein are three point-of-care devices which would not require specialist users and give no significantly different results from hospital methods. The aim of this project was to design, fabricate and use a microfluidic device made from filter paper as a cheaper alternative to current microfluidic devices already available. The creation of channels to direct the movement of fluid within the paper matrix was established by modifying a photolithography method, thereby providing hydrophilic channels surrounded by a hydrophobic barrier. A three dimensional device was constructed entirely from filter paper to incorporate the simultaneous removal, reduction and detection of iron(II) via bathophenanthroline detection for the determination of iron(II) levels in a patient, indicative of the nutritional state of the patient e.g. does the pateitn suffer from anaemia. This method was deemed accurate by comparing the results to a conventional laboratory method (spectrophotometer analysis) completed in a hospital pathology laboratory. No significant difference was observed between results received from the hospital and results found using the paper microfluidic device, 15 μM ± 0.6% SEM versus 15.5 μM ± 0.8% SEM respectively. Two paper devices were developed to allow a quick and reliable measurement assessment of a patient’s renal function. The first for urea, as a simple colour change for a high or low readout of urea levels in serum samples, e.g. ≥ 150 μg/mL then an orange/red colour would be seen on the paper device, indicative of renal failure ≤ 150 ug mL¯¹. The second device used the Jaffe reaction on filter paper as a dipstick assay. No significant difference was observed between results received from the hospital and results found using the paper device 3.92 ± 1.2% versus 3.88 mg mL¯¹ ± 0.6% respectively. These three devices fulfil the aims of the project outline by remaining simplistic to use and are cost effective in both the developing and developed world, whilst maintaining accuracy as seen in the results received from hospital pathology laboratories.
HydraID: hull:10515 Hydra Discover Access Group: public ETD Collection: ETDChemistry
Keywords: Chemistry